Riesgo de problemas de salud mental y rendimiento escolar en estudiantes de un centro educativo Iquitos 2025 - Aspajo Fasanando, Aurora Milagros (2025)
The objective of the study was to determine the association between the risk of mental health problems and academic performance in second-year secondary school students at the Libertador Simón Bolívar Iquitos 2025 educational institution. The research was quantitative, non-experimental, correlational, and cross-sectional in design, with a sample of 103 second-year secondary school students of both sexes enrolled in the morning shift in the year 2025. The technique used was a self-administered survey and documented records. The instruments were the DASS-21 depression, anxiety, and stress scale and the school performance record, applying Fisher Freeman-Halton's exact statistical test to verify the hypothesis. The main findings were: 75,7 % of most students do not present an overall risk of mental health problems. When analyzing specific risks, a considerable sample of 67% was at risk for anxiety, 51.5% for depression, and 51.5% for stress. Regarding academic performance, 50.5% of students rated themselves as in progress, 41.7% as expected achievement, and 7.8% as beginning. Despite the high prevalence of anxiety and depression risk, no statistically significant association was found between the overall risk of mental health problems and academic performance (p=0.130), with the specific risk of stress (p=0.127), anxiety (p=0.856), or depression (p=1.000). In conclusion, there was no significance between the risk of mental health problems and academic performance among second-year high school students at the "Libertador Simón Bolívar" educational institution.